A sol–gel titanium–silicon oxide/organic hybrid dielectric for low-voltage organic thin film transistors. Issue 5 (3rd December 2014) - Yang, Bo-Xuan; Tseng, Chih-Yao; Chiang, Anthony Shiaw-Tseh; Liu, Cheng-Liang
Abstract : A titanium–silicon oxide/organic hybrid dielectric for low-voltage organic thin film transistors (OTFTs) is prepared by a sol–gel process at low temperature. Abstract : We report on the fabrication of low-voltage operating pentacene-based organic thin film transistors (OTFTs), composed of a high k gate dielectric made from titanium–silicon oxide/organic hybrid materials covered with a long alkyl chain having a phosphonic binding group.